Teacher’s Job Satisfaction And Its Relationship With Organizational Commitment In Ethiopian Primary Schools: Focus On Primary Schools Of Bonga Town - Getahun, Teferi; Tefera, Bekalu Ferede; Burichew, Abebe Hunde (European Scientific Journal, ESJ, 2016)
This study explored the extent of organizational commitment and how this may support or hinder a range of job satisfaction of teachers examined in the Ethiopian primary schools.The research employed correlation design. To this end, one hundred and eighteen 118 (58.1%) teachers were selected from six primary schools using simple random sampling technique and participated in the study. The researchers collected the relevant data from teachers using Spector’s (1997) adopted version of job satisfaction survey (JSS) and Meyer and Allen’s (1990) organizational commitment questionnaire (OCQ). The researchers analyzed the data using mean, standard deviation, correlation analysis and t-test. The result showed that there was evidence of positive correlation between teachers’ job satisfaction and their organizational commitment in the sampled schools. Regardless of this, the findings of the study revealed that gender was the only demographic variable that had significant positive relationship with job satisfaction. The other demographic variables such as age, gender, marital status and level of education did not show significant relationship with teachers’ job satisfaction in the sampled schools. Consequent up on this finding it was concluded that schools can enhance the level of teachers’ organizational commitment by creating a more satisfying working environment. As to the demographic variable, since some of the finding contradicts with the existing literature, we need to undertake more studies to have better understanding of the nature of the relationship between teachers demographic variables, job satisfaction and organizational commitment in developing countries context.